Digital Forensic and Organization & Administration: A Review of Journal Articles from 2012 to 2022 - Anissa, Salsabila; Rosnawati, Emy; Khumairoh, Bulqis (Proceedings of The ICECRS, 2023)
This data article presents an analysis of 100 journal articles on digital forensics and "organization & administration" within the realm of law, collected from Lens.org spanning 2012 to 2022. The study aimed to quantify the presence of articles related to these keywords, revealing the University of Edinburgh as the top institution and political science as the most active field. Eoghan Casey and Olivier Ribaux emerged as prolific authors, while the United Kingdom stood out as the most active country, and Elsevier as the primary publisher. This dataset provides valuable insights for further research on digital forensics and its intersection with human-focused aspects.Highlights : Identifies top institution and most active field of study Recognizes prolific authors contributing to the domain Highlights the active country and leading publisher in the field Keywords: digital forensics, organization & administration, journal articles, law, Lens.org